NEUROLOGICAL AND CLINICAL ASPECTS OF ANGELMAN SYNDROME, A NEURO-GENETIC DISORDER - SATYANAND TYAGI,; MOHIT SINGLA,; SACHIN KUMAR., (International Journal of Pharma and Bio Sciences, 2010)
Angelman syndrome (AS) is a neuro-genetic disorder characterized by intellectual and developmental delay, sleep disturbance, seizures, jerky movement’s especially hand-flapping, frequent laughter or smiling, and usually a happy demeanor.Genetically, there is no way to predict this disease prior to its occurrence. There is currently no cure available for Angelman syndrome however symptoms like epileptic seizures can be controlled by the use of one or more types of anticonvulsant medications. Mild laxatives are also used frequently to encourage regular bowel movements and early intervention with physiotherapy is important to encourage joint mobility and prevent stiffening of the joints. In the present article, we have concentrated on neurological and clinical aspects of Angelman syndrome. The aim of present article is to provide in depth knowledge about Angelman syndrome and various aspects related to Angelman syndrome.